Question #8ce4f

2 Answers
Mar 30, 2017

x=(5+-sqrt(5))/2

Explanation:

Note that
color(white)("XXX")color(orange)((x-1)^2)=color(orange)(x^2-2x+1)

So
color(orange)((x-1)^2)color(magenta)(-3x+4)=0
is equivalent to
color(orange)(x^2-2x+1)color(magenta)(-3x+4)=0
or
x^2-5x+5=0
or
color(blue)1x^2color(red)(-5)x+color(green)5=0

Using the quadratic formula:
color(white)("XXX")a quadratic of the form color(blue)ax^2+color(red)bx+color(green)c=0
color(white)("XXX")has solutions x=(-color(red)b+-sqrt(color(red)(b)- 4color(blue)acolor(green)c))/(2color(blue)a)

So color(blue)1x^2color(red)(-5)x+color(green)5=0

has solutions x= (+color(red)5+-sqrt((color(red)(-5))^2-4 * color(blue)1 * color(green)5))/(2 * color(blue)1)

color(white)("XXXXXXXX")=(5+-sqrt(5))/2

Mar 30, 2017

x=5/2 +- sqrt5 /2

Explanation:

Let x-1=y so that the given eq becomes y^2 -3y-3+4=0

Or, y^2 -3y+1=0

Using the quadratic formula, it would be y=(3+-sqrt(9-4))/2

Or, y=3/2 +- sqrt5 /2

So that x=1+3/2 +-sqrt5/2= 5/2 +- sqrt5 /2